Multi-peril pathogen risks to global wheat production: A probabilistic loss and investment assessment - Chai, Yuan; Senay, Senait; Horvath, Diana; Pardey, Philip (Frontiers in Plant Science, 2022)
Crop diseases cause significant food and economic losses. We examined the joint, probabilistic, long-term, bio-economic impact of five major fungal pathogens of wheat on global wheat production by combining spatialized estimates of their climate suitability with global wheat production and modeled distributions of potential crop losses. We determined that almost 90% of the global wheat area is at risk from at least one of these fungal diseases, and that the recurring losses attributable to this set of fungal diseases are upwards of 62 million tons of wheat production per year. Our high-loss regime translates to around 8.5% of the world’s wheat production on average—representing calories sufficient to feed up to 173 million people each year. We estimate that a worldwide research expenditure of $350-$974 million (2018 prices) annually on these five fungal diseases of wheat, let alone other pathogens, can be economically justified, equivalent to 2 to 5 times more than the amount we estimate is currently spent on all wheat disease-related public R&D.